Oxylipins as canine sepsis indicators in vivo and in ex vivo skin organ culture model - Denise Biagini; Chiara Di Franco; Giulia Lazzarini; Vincenzo Miragliotta; Tommaso Lomonaco; Fabio Di Francesco; Angela Briganti (Scientific Reports)
Abstract Sepsis, a life-threatening condition characterized by a dysregulated immune response to infection, remains a significant cause of mortality in both humans and veterinary patients. This study explores oxylipins as potential indicators of sepsis in dogs through in vivo plasma analysis and an ex vivo lipopolysaccharide (LPS)-treated skin organ culture model. By employing a robust analytical platform, 52 oxylipins and 4 polyunsaturated fatty acids were profiled in plasma and skin cultures. Results revealed distinct biochemical and morphological changes, with LPS triggering capillary vasodilation and time-dependent increases in pro-inflammatory mediators such as PGE2 and isoprostanes. Importantly, PGE2 exhibited consistent trends across both models, highlighting its potential as a diagnostic biomarker. This study underscores the utility of the skin organ culture model in mimicking early inflammatory events, offering novel insights into oxylipin dynamics during sepsis and their implications for disease resolution.